A SIMPLIFIED BUT EFFECTIVE METHOD FOR THE QUALITY CONTROL OF MEDICINAL PLANTS BY PLANAR CHROMATOGRAPHY - Eloff, J N; Ntloedibe, D T; van Brummelen, R (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Three of the factors limiting the rational use of herbal medicine are uncertainty on effectivity, uncertainty on safety and variation in quality of the product. Because many herbal medicines have been used over centuries by indigenous peoples, the safety and effectivity is frequently not such a big concern. With more people collecting and distributing herbal medicine, the offered product is however, frequently not what the label indicates either through a genuine mistake, but also through fraud especially where expensive herbal medicine is concerned. Some wrong identifications have already led to serious side effects and deaths. Planar chromatography or thin layer chromatography [TLC] is widely used to verify the identity of plant extracts by determining the chemical fingerprint of the extracts. In a leading publication 17 different extractants, 41 solvent systems and 44 spray reagents have been used to verify the identity of important herbal preparations. We investigated whether a simplified system could not be developed to aid small laboratories in identifying different herbal medicines. We compared the efficacy of different extractants, identified and developed three TLC solvent systems that would separate compounds with low, medium and high polarity and then also investigated the use of several spray reagents. With acetone as extractant and benzene:ethanol:ammonia [9:1:0.1], chloroform:ethylacetate:formic acid [5:4:1] and ethylacetate:methanol:water [10:1.35:1] as TLC solvent system and vanillin-sulphuric acid as spray reagent the identity of 81 samples of more than 50 herbal preparations could be verified on the basis of the chromatograms. The same product from different suppliers usually gave similar chromatograms. More importantly in several cases it was clear that products with the same label were so different that a mistake must have occurred in the labelling. This method has found application in the quality control of the most important African medicinal plants in the recently published African Herbal Pharmacopoeia produced by the Association for African Medicinal Plant Standards (AAMPS).